1979
DOI: 10.1111/j.1469-8137.1979.tb07566.x
|View full text |Cite
|
Sign up to set email alerts
|

ENZYMATIC STUDIES ON THE METABOLISM OF VESICULAR‐ARBUSCULAR MYCORRHIZA. III. ULTRASTRUCTURAL LOCALIZATION OF ACID AND ALKALINE PHOSPHATASE IN ONION ROOTS INFECTED BY GLOMUS MOSSEAE (NICOL. & GERD.)

Abstract: SUMMARYThe ultrastructural distribution of acid and alkaline phosphatase in 6-week-old onion roots infected by Glomus mosseae has been investigated cytochennically. Significant acid phosphatase activity was only observed in the little vacuolated, immature terminal arbuscule branches of the mycorrhizal fungus whilst strong alkaline a-naphthyl phosphatase and /?-glycerophosphatase activities were localized within the vacuoles of the mature arbuscular and intercellular hyphae. In the host cells neither acid nor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 8 publications
5
51
1
1
Order By: Relevance
“…These results were in agreement with the previous observations (Abdel-Fattah and El-Katony 1996, Ibrahim et al 2011, Smith et al 2011, Gosling et al 2013 who stated that mycorrhiza-specific phosphatase (MPSase) was detected only in the root extract colonized with mycorrhizal fungi as compared to nonmycorrhizal root extract. The close relationship between the mycorrhizal growth responses and the intensity of the mycorrhizal colonization support the hypothesis that the phosphatase enzymes are somehow involved in the assimilation of P by AMF (Gianinazzi et al 1979, Abdel-Fattah 2001. Addition of soluble phosphate to soil significantly decreased the levels of the mycorrhizal colonization in root tissues of the soybean plants and therefore reduced the activities of acid and alkaline phosphatase in the mycorrhizal root extracts of the plants.…”
Section: Discussionsupporting
confidence: 69%
“…These results were in agreement with the previous observations (Abdel-Fattah and El-Katony 1996, Ibrahim et al 2011, Smith et al 2011, Gosling et al 2013 who stated that mycorrhiza-specific phosphatase (MPSase) was detected only in the root extract colonized with mycorrhizal fungi as compared to nonmycorrhizal root extract. The close relationship between the mycorrhizal growth responses and the intensity of the mycorrhizal colonization support the hypothesis that the phosphatase enzymes are somehow involved in the assimilation of P by AMF (Gianinazzi et al 1979, Abdel-Fattah 2001. Addition of soluble phosphate to soil significantly decreased the levels of the mycorrhizal colonization in root tissues of the soybean plants and therefore reduced the activities of acid and alkaline phosphatase in the mycorrhizal root extracts of the plants.…”
Section: Discussionsupporting
confidence: 69%
“…A possible explanation for this is that the activity of the host membrane is modified with its rapid proliferation around the developing fungus so that less wall material is produced. However studies up to now, including the present observations have not been able to demonstrate any morphological, cytochemical or enzymic dif ferences between the invaginated plasmalemma of a VA mycorrhizal cell and the peripheral plasmalemma of an uninfected cell (Dexheimer et al 1979, Bonfante-Fasolo et al 1981, Marx et al 1982, Gianinazzi et al 1983). An alternative explanation is that the VA fungus somehow presents the process of polymerization and deposition of cell wall material by the host cell.…”
Section: Resultscontrasting
confidence: 51%
“…Numerous studies of different vesicular-arbuscular (VA) mycorrhizal associa tions have shown that their ultrastructural organisation is very similar, independent of the plant or fungus involved, and that the main aspects of the host-endophyte interface are identical (see for example Scannerini and Bellando 1968, Cox and Sanders 1974, Kaspari 1975, Kinden and Brown 1975, Bonfante-Fasolo 1978, Scannerini and Bonfante-Fasolo 1979, Dexheimer et al 1979, Holley and Peterson 1979, Bonfante-Fasolo et al 1981. Previous pub lications often illustrate membranous vesicles or tubules associated with the plant or fungus in the region of the intracellular host-arbuscule interface.…”
mentioning
confidence: 99%
“…These results suggest that AMF benefited by the decomposed products (Talbot et al 2008). However, AMF are known to excrete alkaline phosphatases (Gianinazzi et al 1979), which could partially explain the low acid phosphatase activity found under the Carrasco vegetation. AMF root colonization in the litter bags was also high in the E. camaldulensis plots but low in those at the preserved site, which confirmed the role of microorganisms in the release of organic phosphorus.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%